AN ANALYSIS OF MORAL VALUES IN LALALAND’S FILMATMAN V SUPERMAN MOVIE “DAWN OF JUSTICE” BY ZACK SYNDER - JUNIAR .; RIDWAN SYAHPUTRA (JURNAL ILMIAH SIMANTEK, 2019)
This research is aimed at getting the result of moral value in Batman V Superman movie "Dawn of Justice" directed by ZackSynder. The method of research that is used in this research is descriptive qualitative method. This reserach also used twoapproaches, psychological approach and structural approach. Technique of collecting data by collecting VCD and watchingthe film. The technique analysis the data uses qualitative research. Finally, the result of this research show that this movieportary morality from Batman V Superman movie "Dawn of Justice" by Zack Synder. This movie teach us how to be a betterperson by seeing the positive of moral value in the movie and did not take anything negative in the film. Based on thediscussion, The writer want to tell the moral value which showed in Batman V Superman movie "Dawn of Justice" by ZackSynder to all of the readers, and the writer also hope the readers could take the main point from it.